Multifunctional Magnetic Gold Nanomaterials for Cancer. Issue 9 (September 2019) - Das, Pradip; Fatehbasharzad, Parisa; Colombo, Miriam; Fiandra, Luisa; Prosperi, Davide
Abstract : The integration of multiple imaging and therapeutic agents into a customizable nanoplatform for accurate identification and rapid prevention of cancer is attracting great attention. Among the available theranostic nanosystems, magnetic gold nanoparticles are particularly promising as they exhibit unique physicochemical properties that can support multiple functions, including cancer diagnosis by magnetic resonance imaging, X-ray computed tomography, Raman and photoacoustic imaging, drug delivery, and plasmonic photothermal and photodynamic therapies. This review gives an overview of recent advances in the fabrication of multifunctional gold nanohybrids with magnetic and optical properties and their successful demonstration in multimodal imaging and therapy of cancer. Concerns around toxicity of these nanomaterials are also discussed in view of an imminent transition to clinical practice. Highlights: Fundamental strategies for the synthesis of gold nanostructures with desirable optical properties are well developed, which is an important requirement for the design and fabrication of multifunctional magnetic gold nanomaterials. Using magnetic gold nanomaterials as a contrast agent in multimodal imaging overcomes the limitations of each individual imaging technique in early stage cancer diagnosis by providing enhanced spatial resolution and improved sensitivity. Synergistic effects of multiple therapies using a magnetic gold nanomaterials-based therapeutic agent are more effective in the treatment of cancer compared with single therapy. Cancer theranostics based on a combination of multiple imaging and therapies show excessive potentiality to fight against cancer, in which biocompatible multifunctional magnetic gold nanomaterials can play a significant role in future clinical translation.